2020
DOI: 10.3389/fnbeh.2020.00089
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic Reappraisal-Based Implementation Intention Produces Early and Sustainable Emotion Regulation Effects: Event-Related Potential Evidence

Abstract: Implementation intention has proven effective in regulating intense emotions but is found to be difficult when instructed regulation is used. Here, we aim to test whether automatic reappraisal-based implementation intention (RII) downregulates intense negative emotion more efficiently than controlled reappraisal (CR) using a two-phase event-related potential (ERP) experiment. In the regulation phase, both RII and CR decreased subjective experiences of negative emotion relative to passive watching, irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Since no microstate differences emerged from the repeated application of the ER strategies, the training effect might have been too small to detect, especially because it is smaller for down- than up-regulation 79 . Relating this finding to EEG studies of re-exposure 36 , 80 is not appropriate because we presented new stimuli in the last block. Moreover, studies on ER training often either focus on behavioral outcomes or on improving ER by training a different skill altogether 81 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Since no microstate differences emerged from the repeated application of the ER strategies, the training effect might have been too small to detect, especially because it is smaller for down- than up-regulation 79 . Relating this finding to EEG studies of re-exposure 36 , 80 is not appropriate because we presented new stimuli in the last block. Moreover, studies on ER training often either focus on behavioral outcomes or on improving ER by training a different skill altogether 81 84 .…”
Section: Discussionmentioning
confidence: 99%
“…We also have to assume that the expected training effect might have been too small to detect. Relating this finding to EEG studies of re-exposure (Chen et al, 2020;Thiruchselvam et al, 2011) is not appropriate, as we did not use the same stimuli in the last block as in the blocks before. Moreover, studies on ER training either focus on behavioral outcomes or aim to improve ER by training a different skill altogether (Jazaieri et al, 2014;Nesayan et al, 2017;Schuppert et al, 2009;Wadlinger & Isaacowitz, 2011).…”
Section: Effects Of Er Strategies On Different Microstatesmentioning
confidence: 99%
“…Implicit ER is a goal-driven process in which individuals adjust their emotions unconsciously or automatically. Research in adults has revealed that in comparison to the explicit use of adaptive ER strategies, employing implicit ER with the same strategies can also reduce subjective experiences or physiological indicators of negative emotions without the substantial involvement of subjective endeavors and consumption of cognitive resources [34][35][36][37]. In contrast, because the processes of explicit ER are associated with greater cognitive and physiological costs than those of implicit ER, the implementation of explicit ER may not always be successful and realize positive effects in regulating emotions [20].…”
Section: Adolescent Development and Emotion Regulationmentioning
confidence: 99%